The grammatical categories peculiarities of the Ukrainian language (on the grammars material of the 20 – 30th of the XXth century) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with the features of the main grammatical categories of the Ukrainian language, fixed in the Ukrainian grammars of the 20 – 30th of the XXth century, in comparison with the Russian. The basic causes and the means of expression of the language differences were summarized on the grammatical level.
Keywords: grammatical category; grammeme; category of gender; category of number; category of case; category of mode; category of voice